Thyroid Function and Metabolic Syndrome in Children and Adolescents with Neuromotor Disability - Valeria Calcaterra; Giacomo Biganzoli; Simona Ferraro; Alessandra Mari; Anna Mandelli; Valentina Fabiano; Patrizia Carlucci; Gloria Pelizzo; Elena Zoia; Giulia Lanfranchi; Silvana Castaldi; Patrizia Boracchi; et al. (Children, 2022)
Thyroid function plays a crucial role in nervous system integrity and metabolic homeostasis. We evaluated the pattern of TSH, FT4 and FT3 release in children with neuromotor impairment (NI) in relationship with metabolic syndrome (MS). We enrolled 55 patients with NI and 30 controls. Clinical parameters, thyroid function and MS presence were recorded. Principal component analysis (PCA), cluster analysis, and logistic regression models were performed. MS was detected in 54.5% of patients. Four clusters were identified: the first one included only controls and, contrasting with cluster 4, was exclusively characterized by children with disability and MS. This latter showed increased FT4 and FT3 and decreased TSH levels. Cluster 2, characterized by disability without MS showed high FT4 and FT3, whereas cluster 3 with low FT4 and FT3 mainly included disability (90%) and showed prevalent MS (57%). The association between TSH and NI is represented by a U-shape structure. The TSH, FT3 and FT4 release patterns may reflect thyrotropic adaptation, allostatic response and compensatory mechanisms. These mechanisms, found in both MS and disability, show that the odds of having a condition of NI with or without MS increase as the TSH values deviate, in both directions, from a value of 2.5 mLU/mL.